Differentiation Strategy and Market Deregulation: Local Telecommunication Entry in the Late 1990s - Shane M Greenstein; Michael J. Mazzeo (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
The authors examine the role of differentiation strategies for entry behavior in markets for local telecommunication services in the late 1990s. Whereas the prior literature has used models of interaction among homogenous firms, this research is motivated by the claim of entrants that they differ substantially in their product offerings and business strategies. Exploiting a new, detailed data set of Competitive Local Exchange Carriers (CLECs) entry into over 700 U.S. cities, the authors take advantage of recent developments in the analysis of entry and competition among differentiated firms. They test and reject the null hypothesis of homogeneous competitors. They also find strong evidence that CLECs account for both potential market demand and the business strategies of competitors when making their entry decisions. This suggests that firms' incentives to differentiate their services should shape the policy debate for competitive local telecommunications.
Keywords: 330; Markteintritt; Produktdifferenzierung; Telekommunikation; Deregulierung; USA